2015
DOI: 10.2174/1573409910666141031093504
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Feature of the Non-Peptide Ligand Interactions with Mice Mu-Opioid Receptors

Abstract: By binding to and activating the G-protein coupled μ-, κ- and δ-opioid receptors in the central nervous system, opiates are known to induce analgesic and sedative effects. In particular, non-peptide opioid ligands are often used in clinical applications to induce these therapeutically beneficial effects, due to their superior pharmacokinetics and bioavailability in comparison to endogenous neuropeptides. However, since opioid alkaloids are highly addictive substances, it is necessary to understand the exact me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…Hydrophobic interactions were formed between camel LVV-hemorphin-7 and Tyr328, which is consistent with a previous report that indicated that hemorphin interacts with Tyr326 of mouse MOR 49,51,56 . The interaction with Trp320 on TM7 is also consistent with previous studies 51,57,58 . Interestingly, camel LVV-hemorphin-7 interacted with key residues in the binding pocket for a longer duration than non-camel hemorphin (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hydrophobic interactions were formed between camel LVV-hemorphin-7 and Tyr328, which is consistent with a previous report that indicated that hemorphin interacts with Tyr326 of mouse MOR 49,51,56 . The interaction with Trp320 on TM7 is also consistent with previous studies 51,57,58 . Interestingly, camel LVV-hemorphin-7 interacted with key residues in the binding pocket for a longer duration than non-camel hemorphin (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…LVVYPWTRRF interacted for a longer duration than LVVYPWTQRF with Thr220, Glu231, and Tyr328 in the human MOR model. The corresponding residues in the murine MOR – Thr200, Glu299, and Tyr326 – have been shown to interact with agonists 49,51,56,58 . RMSF values were found to be high for IL-3 residues when bound to camel LVV-hemorphin-7.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the binding modes of different ligands at the μ, δ-, and κ-OR [5,6163]. For instance, based on docking models, Noori et al proposed two main binding regions in opioid receptors that might correlate with agonists and antagonists in terms of depth within the receptor, following a relationship between the affinity of the ligand and the proximity to the extracellular side [64]. Similarly, it could be hypothesized that the binding recognition profile of biased ligands might be characteristic and allow one to discriminate biased from nonbiased ligands.…”
Section: Binding Models Of Biased Ligandsmentioning
confidence: 99%